2018
DOI: 10.1016/j.geomorph.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Last Glacial aeolian landforms and deposits in the Rhône Valley (SE France): Spatial distribution and grain-size characterization

Abstract: In the Rhône Valley, a north-south oriented Cenozoic rift in southeast France, thick Pleistocene loess deposits have been recognized since the beginning of the last century. These loess records, which are disconnected from the North European Loess Belt (NELB), are of significant interest to document the evolution of perimediterranean landscapes and environments during the Last Glacial. To overcome the poor precision of available aeolian distribution maps, aeolian deposits were mapped using the topsoil textural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 214 publications
3
28
0
Order By: Relevance
“…Recent studies in the Po plain in Italy (Cremaschi, 1990;Cremaschi et al, 2015;Zerboni et al, 2015) and Croatia (Wacha et al, 2018), as well as in the Ebro (Boixadera et al, 2015) and Tagus basins (Wolf et al, 2019(Wolf et al, , 2018 in Spain suggested, however, that Pleistocene loess covers considerable areas in peri-Mediterranean regions. Last Glacial loess is also widespread in the Rhône Valley, southeast France (Bosq et al, 2018(Bosq et al, , 2020 and references therein). These deposits have specific characteristics when compared to loess from the North-European Loess Belt (NELB), including a coarser texture (main grain-size mode around 60 μm), polymodal grain-size distribution, locally great thickness but discontinuous spatial distribution, high carbonate content and abundant synsedimentary bioturbation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in the Po plain in Italy (Cremaschi, 1990;Cremaschi et al, 2015;Zerboni et al, 2015) and Croatia (Wacha et al, 2018), as well as in the Ebro (Boixadera et al, 2015) and Tagus basins (Wolf et al, 2019(Wolf et al, , 2018 in Spain suggested, however, that Pleistocene loess covers considerable areas in peri-Mediterranean regions. Last Glacial loess is also widespread in the Rhône Valley, southeast France (Bosq et al, 2018(Bosq et al, , 2020 and references therein). These deposits have specific characteristics when compared to loess from the North-European Loess Belt (NELB), including a coarser texture (main grain-size mode around 60 μm), polymodal grain-size distribution, locally great thickness but discontinuous spatial distribution, high carbonate content and abundant synsedimentary bioturbation.…”
Section: Introductionmentioning
confidence: 99%
“…This paper has the following objectives: (1) high-resolution multi-proxy analysis of two sections (Collias and Lautagne) representative of the loess-palaeosol sequences of the Rhône Valley, southeast France, (2) development of an accurate chronological framework using a hierarchical Bayesian model based on OSL and AMS 14 C ages of the section of Lautagne, and Bertran et al (2016) with additional data from Bosq et al (2018) and Lindner et al (2017), showing the location of the sections studied in the Rhône Valley and within the Rhône catchment (red line). The British-Irish Ice Sheet (BIIS) and Scandinavian Ice Sheet (SIS) are from Hughes et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another potential limitation is that we used only three climatic predictors to define the environmental background. It is possible that other factors, such as the presence of cold deserts (Bertran et al, 2013;Bosq et al, 2018) and periglacial conditions, which were not considered in this study, could have influenced these hunter-gatherer populations, their settlement systems and cultural adaptations, and in turn the ecological niche that they exploited. Including these predictors would be a means to evaluate the results and hypotheses presented here.…”
Section: Discussionmentioning
confidence: 99%
“…Noailles burin contexts in Italy are also interpreted as being younger than those in France (Touzé, 2013), but the majority of their associated radiocarbon ages were produced decades ago (non-AMS) and evaluations of their archaeological association are lacking, thus rendering any comparison to the French archaeological record unreliable at present. Siddall et al, 2003;Glaciers cover: Ehlers & Gibbard, 2004; Periglacial cold deserts: Bertran et al, 2013;Bosq et al, 2018 Taking into account these limitations, we constrain our analysis to the comparison of two adjacent regions that are thought to represent coherent territories during the Middle Gravettian: 1) the Pyrenees piedmont and plateau, based on assemblages that are regionally coherent with respect of lithic typo-technology (i.e. contexts that contain Noailles burins and in which the Raysse method is absent) and raw material circulation for the entirety of the Middle Gravettian (Foucher et al, 2008;Foucher, 2013;Simonet, 2009aSimonet, , 2017Banks et al, 2019), and 2) the area constrained to the south by the Garonne River Valley and by the most northerly sites where the "Raysse method" has been observed (Klaric, 2017).…”
Section: Archaeological Datamentioning
confidence: 99%
See 1 more Smart Citation